The Effectiveness of Psychodrama with the Content of Life Skills on Loneliness, Happiness, Affective Relationship and Parents’ Social Support in Adolescent Girls Dependent on the Cellphone - Safura Amoosoltani; Fariba Yazdkhasti; Hamidreza Oreyzi; Javad Abbasi Jondani (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2021)
The purpose of the present study was to examine the effectiveness of psychodrama with the content of life skills on loneliness, happiness, affective relationships and parents’ social support in adolescents dependent on the cellphone. The design of this study was experimental and pretest-posttest and follow-up with the control group. The study population included female high school students in Khomeinishahr. The statistical sample of this study included 30 students dependent on the cellphone who were selected by cluster sampling and randomly assigned to two groups of 15 participants. To collect data. the scale of mobile dependence MPAI Lung (2007), Affective family climate of Hill Burn (1964), Parents' Social Support of Prosidano and Heller (1983), Happiness OHQ (1987), and UCLA Loneliness (1980) was used. The results of multivariate covariance analysis showed that sessions of psychodrama with the content of life skills were effective in reducing loneliness, increasing happiness, improving adolescent affective relationships and social support of their parents and these effects stayed stable in follow-up (p